Bioinformatic identification of hub genes and key pathways in neutrophils of patients with acute respiratory distress syndrome. Issue 15 (April 2020) - Hu, Lan; Zhao, Tianxin; Sun, Yuelin; Chen, Yingfu; Bai, Ke; Xu, Feng
Abstract : Abstract: Acute respiratory distress syndrome (ARDS) is characterized as a neutrophil-dominant disorder without effective pharmacological interventions. Knowledge of neutrophils in ARDS patients at the transcriptome level is still limited. We aimed to identify the hub genes and key pathways in neutrophils of patients with ARDS. The transcriptional profiles of neutrophils from ARDS patients and healthy volunteers were obtained from the GSE76293 dataset. The differentially expressed genes (DEGs) between ARDS and healthy samples were screened using the limma R package. Subsequently, functional and pathway enrichment analyses were performed based on the database for annotation, visualization, and integrated discovery (DAVID). The construction of a protein–protein interaction network was carried out using the search tool for the retrieval of interacting genes (STRING) database and the network was visualized by Cytoscape software. The Cytoscape plugins cytoHubba and MCODE were used to identify hub genes and significant modules. Finally, 136 upregulated genes and 95 downregulated genes were identified. Gene ontology analyses revealed MHC class II plays a major role in functional annotations. SLC11A1, ARG1, CHI3L1, HP, LCN2, and MMP8 were identified as hub genes, and they were all involved in the neutrophil degranulation pathway. The MAPK and neutrophil degranulation pathways in neutrophils were considered as key pathways in the pathogenesis of ARDS. This study improves our understanding of the biological characteristics of neutrophils and the mechanisms underlying ARDS, and key pathways and hub genes identified in this work can serve as targets for novel ARDS treatment strategies.